2014
DOI: 10.1089/ten.tea.2013.0455
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Matrix Nanotopography and Stiffness on Vascular Smooth Muscle Cell Function

Abstract: Vascular smooth muscle cells (vSMCs) retain the ability to undergo modulation in their phenotypic continuum, ranging from a mature contractile state to a proliferative, secretory state. vSMC differentiation is modulated by a complex array of microenvironmental cues, which include the biochemical milieu of the cells and the architecture and stiffness of the extracellular matrix. In this study, we demonstrate that by using UV-assisted capillary force lithography (CFL) to engineer a polyurethane substratum of def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 68 publications
(64 reference statements)
4
63
0
Order By: Relevance
“…While several other methods exist wherein cellular shape and structure could be modulated while maintaining cell-cell contact, 11b, c, 23 our single cell model represents the smallest functional unit of the VIC and thus an important first step in understanding the role of VIC shape on its biology and function. Shorter and wider VICs generated less contractile stress and were at a less biosynthetic and proliferative state, while elongated narrower VICs had greater contractile stress generation, more biosynthesis, increased proliferation and α-SMA activation, correlating with greater organization of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…While several other methods exist wherein cellular shape and structure could be modulated while maintaining cell-cell contact, 11b, c, 23 our single cell model represents the smallest functional unit of the VIC and thus an important first step in understanding the role of VIC shape on its biology and function. Shorter and wider VICs generated less contractile stress and were at a less biosynthetic and proliferative state, while elongated narrower VICs had greater contractile stress generation, more biosynthesis, increased proliferation and α-SMA activation, correlating with greater organization of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…12,22 A small amount of polymer was drop-dispensed onto a glass coverslip (No.1, 25mm, Fisher Scientific, Pittsburgh, PA, USA), and a PUA nanopattern mold on PET film was placed onto the polymer drop. The polymer spontaneously filled the cavity of the mold through capillary action.…”
Section: Methodsmentioning
confidence: 99%
“…8-11 Recent studies have suggested that nanotopographic cues and substrate rigidities are important factors affecting the morphology and behavior of vascular cell types, including endothelial cells. 7,12-14 …”
Section: Introductionmentioning
confidence: 99%
“…[60, 61] Briefly, polymer master molds were created by first dispensing PUA precursor solution onto a patterned silicon wafer that was generated using standard photolithography. A nanopattern comprising a series of parallel ridges and grooves with 800 nm × 800 nm × 600 nm (ridge width × groove width × ridge height) dimensions was used for these studies.…”
Section: Methodsmentioning
confidence: 99%